2017
DOI: 10.1021/acs.bioconjchem.6b00578
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Membrane Fusion Triggered by Strain-Promoted Alkyne–Azide Cycloaddition

Abstract: Artificial systems for controlled membrane fusion applicable for drug delivery would ideally use triggers that are orthogonal to biology. To apply the strain-promoted alkyneazide cycloaddition (SPAAC) to drive membrane fusion, ODIBO lipid 1 was designed, synthesized and studied alongside ADIBO-lipids 2–4 to assess fusion with liposomes containing azido-lipid 5. Lipids 1–2 were first shown to be effective for liposome derivatization. Next, fusion was evaluated using liposomes containing 1 and varying ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…We have previously found that heating of liposomesc an be necessary to achievee ffects such as liposomef usion. [45] Different control sets were also tested using the exact same liposomef ormulation by treating with only buffer or with heat-denatured enzyme, leadingt od iminished fluorescencec hanges (background releaser anging from % 8-12 %, Figure 1A). Similar results were also observed for liposomes lacking ERL in which this lipid was replaced by PC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that heating of liposomesc an be necessary to achievee ffects such as liposomef usion. [45] Different control sets were also tested using the exact same liposomef ormulation by treating with only buffer or with heat-denatured enzyme, leadingt od iminished fluorescencec hanges (background releaser anging from % 8-12 %, Figure 1A). Similar results were also observed for liposomes lacking ERL in which this lipid was replaced by PC.…”
Section: Resultsmentioning
confidence: 99%
“…After screening a variety of different lipid mixtures, liposomes composed of 30 % ERL , 50 % DOPE, 10 % PC and 10 % DOTAP treated with 0.45 U of porcine liver esterase and incubated in a 30 °C water bath in between measurements showed an ≈30 % decrease in fluorescent intensity upon esterase treatment within 40 minutes (Figure A and Table S1, Entry 1). We have previously found that heating of liposomes can be necessary to achieve effects such as liposome fusion . Different control sets were also tested using the exact same liposome formulation by treating with only buffer or with heat‐denatured enzyme, leading to diminished fluorescence changes (background release ranging from ≈8–12 %, Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous model systems for membrane fusion have been developed in recent years, all of which have employed a diverse range of molecules as fusogens. Examples of such fusogens include: hydrogen bonding motifs 1 , DNA [2][3][4][5][6][7][8][9][10][11] , PNA [12][13][14] , coiled-coil peptides [15][16][17][18] , and small molecule recognition motifs [19][20][21][22][23] . These systems exhibit varying efficiencies of fusion: some only facilitate hemifusion, or lipid-mixing; whereas others promote full fusion, resulting in content-mixing.…”
mentioning
confidence: 99%
“…The addition of alkyne- or azide-functional moieties in the molecular structure of amphiphiles coupled with the formation of triazoles provide various opportunities for functionalization and modification of vesicular surfaces 2426 . These synthetic amphiphiles can be incorporated in lipid bilayers and further reacted with complementary molecules without damaging the vesicles 27,28 . Moreover, in the synthesis of 1,2,3-triazoles, the CuAAC reaction is an effective chemoselective and water-tolerant ligation tool that can be used for synthesizing stable cycloaddition products, such as novel phospholipids, to induce growth and splitting of vesicles 19,23 .…”
Section: Resultsmentioning
confidence: 99%